PENGARUH KOMPENSASI, PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DENGAN LOYALITAS KARYAWAN SEBAGAI VARIABEL INTERVENING - Mahendra, Novian Wahyu; Sutrisno, Sutrisno; Meiriyanti, Rita (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This research aims to determine the effect of providing compensation, job training, and work motivation on employee performance with employee loyalty as an intervening variable at UMKM HM Putra Emping. Based on this, this research is entitled "The Effect of Compensation, Job Training, and Work Motivation on Employee Performance with Employee Loyalty as an Intervening Variable (Case Study of UMKM HM Putra Emping in Batang Regency)". The population in this study was 50 employees. The sampling method used in this research was the census sampling method of 50 respondents. The data used is primary data by means of a questionnaire. Data analysis uses path analysis. The findings in this study conclude that compensation has a positive and significant effect on employee performance, job training has no significant effect on employee performance, work motivation has no effect on employee performance, employee loyalty has no effect on employee performance, compensation and work training have no significant effect on employee loyalty. , work motivation has a positive and significant effect on employee loyalty. Compensation has an effect on employee performance through employee loyalty as mediation, job training has a significant effect on employee performance through employee loyalty as mediation, and motivation has no effect on employee performance through employee loyalty as mediation